Impact of multi-scale moisture transport on durability of hardened cement pastes - Chemmi, Houria; Petit, Dominique; Levitz, Pierre; Korb, Jean-Pierre; Bérard, Mathieu (Diffusion Fundamentals, 2009)
We report on proton NMR relaxation of hardened Grey CEM I paste with two controlled degree of relative humidity. The comparison between these two aged materials evidences that the moisture transport only occurs on the meso and capillary scales. The proton population distribution vs T1 follows power laws with a negative exponent in the nanopore-mesopore pore scale, and a positive exponent in the mesopore-capillary pore scale. This opposite exponent sign shows that the spatial hierarchical proton distribution behaves like a surface and volume distribution on short and large scales, respectively.